Cross-media authentication and verification emerging research and opportunities - Katsaounidou, Anastasia, 1990- (Advances in multimedia and interactive technologies (AMIT) book series., 2019)
"As media becomes more readily available in the digital age, it also becomes more vulnerable to tampering and manipulation, making techniques for verifying reliable news and media sources essential. Understanding online technologies' role in shaping the media environment allows for insight into the correlations between the rapidly transforming media landscape and its unwanted effect on news and content tampering. Cross-Media Authentication and Verification: Emerging Research and Opportunities is a collection of innovative research on the methods and applications of verifying the newsgathering and publishing process. While highlighting topics including human authentication, information evaluation, and tampered content, this book is ideally designed for researchers, students, publishers, and academicians seeking current research on media authenticity and misinformation"--Publisher's description.